Paraphilias. Issue 6 (November 2015) - Konrad, Norbert; Welke, Justus; Opitz-Welke, Annette
<x xml:space="preserve">Abstract</x> Purpose of review The concept of paraphilia still carries an 'unwanted burden' of sexual norms because the pathologization of some sexual practices as paraphilic disorders is still based on the assumption that normal sexuality should be genitally organized with the aim of reproduction. The aim of this review is to give an impression of the ongoing discussion about the changes introduced with the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and the results of recent research in this area. Recent findings The release of DSM-5 in the spring of 2013 introduced a distinction between paraphilias and paraphilic disorders, implying a destigmatization of consenting adults engaging in unusual sexual behaviour. According to DSM-5 diagnostic criteria, paedophilic disorder is the only paraphilic disorder without an 'in remission' and an 'in a controlled environment' specifier. Today, antiandrogen treatment is offered to sex offenders in many countries as an additional treatment strategy alongside psychotherapy. Summary The introduction of DSM-5 offers the possibility to distinguish between paraphilia and paraphilic disorders. The aetiology of paraphilias is still unknown. Paraphilias are much more common in men than in women, but the reasons for this difference remain unknown. So far there is no clear consent on the best therapeutic approach for a paraphilic disorder.